Kiribati : 2013 Article IV Consultation-Staff Report; Informational Annex, Debt Sustainability Analysis, Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Kiribati. (IMF Staff Country Reports; Country Report, 2013)
Kiribati is one of the poorest and most remote microstates in the Pacific. It is highly dependent on volatile fishing license fees, remittances, and donor assistance. The challenge is to implement fiscal and structural reforms to help ensure fiscal sustainability, promote private sector development, and increase its resilience to external shocks. Fully using its marine potential beyond fishing license fees will help to improve fiscal revenues and growth opportunities. More generally, private sector development is critical for both increasing growth and reducing fiscal pressures.